Detrended Cross-Correlation Analysis of Biometric Signals used in a - Ursulean, R.; Lazar, A.-M. (Elektronika ir Elektrotechnika, 2009)
The paper presents a study that aims to facilitate the development of an authenticating method, based on biometric signals. Considering a recently introduced method (2008) called the detrended cross-correlation analysis, the authors showed the long-term correlations and anti-correlations of different electroencephalographic signals, which could lead to a smaller number of electrodes in such an authentication method. The correlation coefficient was computed for different pairs of electrodes, for a large number of samples, leading to an acceptable margin of error. Further work in this field could lead to valuable results in analyzing the EEG signals in different pathologies. Ill. 7, bibl. 11 (in English; summaries in English, Russian and Lithuanian).